2011
DOI: 10.1210/en.2010-1166
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of MT1-MMP and MMP-2 by Leptin in Cardiac Fibroblasts Involves Rho/ROCK-Dependent Actin Cytoskeletal Reorganization and Leads to Enhanced Cell Migration

Abstract: Altered leptin action has been implicated in the pathophysiology of heart failure in obesity, a hallmark of which is extracellular matrix remodeling. Here, we characterize the direct influence of leptin on matrix metalloproteinase (MMP) activity in primary adult rat cardiac fibroblasts and focus on elucidating the molecular mechanisms responsible. Leptin increased expression and cell surface localization of membrane type 1 (MT1)-MMP, measured by cell surface biotinylation assay and antibody-based colorimetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 43 publications
3
47
0
Order By: Relevance
“…The disassembly of F-actin cytoskeleton inhibits migration of cardiac fibroblasts [20] , and the inhibition of F-actin assembly has also been proved to inhibit the fibroblast-myofibroblast transition [21] . An in vivo study has also shown that actin cytoskeleton remodeling attenuates myocardial fibrosis following myocardial infarction in rats [22] .…”
Section: Discussionmentioning
confidence: 99%
“…The disassembly of F-actin cytoskeleton inhibits migration of cardiac fibroblasts [20] , and the inhibition of F-actin assembly has also been proved to inhibit the fibroblast-myofibroblast transition [21] . An in vivo study has also shown that actin cytoskeleton remodeling attenuates myocardial fibrosis following myocardial infarction in rats [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of RhoA/ROCK signaling is known to be involved in the regulation of actin cytoskeletal remodeling (40), which has recently been recognized to mediate the trafficking of membrane type 1-MMP (MT1-MMP) to the cell surface (41)(42)(43). MT1-MMP is a transmembrane protease that cleaves extracellular pro-MMP-2.…”
Section: Ep3a/b Modulates Hypoxia-induced Mmp-2/tgf-β1 Activation By mentioning
confidence: 99%
“…These observations indicate that EP3α/β-mediated actin cytoskeletal remodeling regulates intracellular MT1-MMP transportation through activation of Rho GTPase. CD44, a hyaluronic acid receptor, is believed to interact with the hemopexin-like domain of MT1-MMP (41) and to link MT1-MMP with actin filaments through direct CD44 binding to F-actin (41,43). As such, leptin mediates myocardial matrix remodeling by regulating the cell-surface location of MT1-MMP in cardiac fibroblasts via Rho GTPase-mediated actin polymerization, which facilitates the development of heart failure in obesity (43,64).…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…(i) MMP14 modulates glycolysis and is regulated by leptin, the famous obese gene product (38). (ii) Insulin receptor substrate 4 (IRS4), in addition to its known function in insulin-Akt-mTOR signaling, directly binds to and modulates signaling through the leptin receptor (39).…”
Section: Functions Of Midas-containing Mrnas Concentrate On Developmementioning
confidence: 99%